Atypical Transmissible Venereal Tumor in Dogs - Gritzenco, Júlia das Graças; Cabral, Adilson Paulo Marchioni [UNESP]; Albuquerque, Ana Paula Lourenção de; Goulart, Juliana das Chagas; Sanches, Felipe Jacques [UNESP]; Merlini, Natalie Bertelis; Gasser, Beatriz [UNESP]; Marcusso, Paulo Fernandes (Universidade Federal do Rio Grande do Sul, 2022)
Background: The Transmissible Venereal Tumor (TVT), classified as a round cell tumor, is considered one of the oldest existing tumors. It affects dogs all over the world and has a contagious characteristic. Despite the good response to clinical treatment in most cases, it can sometimes have non-classical presentations and even different behavior. Thus, the present study aims to report 3 cases of atypical TVT treated at the Veterinary Medical Teaching Hospital of the State University of Maringá (UEM) in Umuarama, Paraná, aiming to describe the epidemiology and clinical-pathological aspects, focusing on the diagnostic method used, the treatment of choice and the clinical follow-up of each case. Cases: Case records of 3 intact male mongrel dogs with atypical Transmissible Venereal Tumor (case 1: intranasal; case 2: intra-abdominal and case 3: cutaneous with lymph node metastasis) were reviewed regarding history, clinical signs, duration of clinical signs, examination findings, results and findings of complementary exams (hematological, biochemical, radiographic, ultrasonographic and cytological), treatment, follow-up and final result. Case 1: had an ulcerated mass in the nasal plane causing significant airway obstruction and respiratory difficulty. Case 2: had a lesion in a typical location (penile mucosa in the glans area) but with a large intra-abdominal mass in the lumbar paravertebral region, causing compression of important structures. Case 3: on the other hand, had cutaneous TVT with several ulcerated plaque lesions all over the skin, in addition to popliteal lymph node enlargement due to metastasis later confirmed by microscopy. All dogs reported were mixed breed, intact males with free access to the street. Despite the fact that each patient had their own anatomical tumor characteristics, they were all diagnosed through cytological examination and all classified as lymphocytic TVT. The standard treatment for this neoplasm was instituted; the chosen chemotherapy was vincristine sulfate at a dose of 0.75 mg/m2 intravenously every 7 days for 5-7 weeks. In addition, all 3 animals needed supportive treatment due to anorexia, bacterial contamination secondary to injuries, dehydration and pain. Discussion: Usually, TVT is not considered malignant, not causing metastasis, however it is now known that its behavior has changed a lot and more and more cases of metastatic or highly infiltrative TVT have been reported. The 3 cases presented in this report had epidemiological characteristics as mentioned in the literature, but the location, macroscopic and radiographic characteristics are uncommon for this neoplasm, that is, with an atypical tumor presentation. This demonstrates the importance of a good clinical evaluation and, especially, of the cytological exam, which was essential for the definitive diagnosis for the three cases presented. It is speculated that more “aggressive” cases of TVT may be correlated with the plasmacytic cytological type, however none of the patients described here had this cytological presentation. Thus, the clinician must be aware of the risk factors associated with this neoplasia, because even in non-classical presentations, the lymphocytic cell morphological characteristic was present and the patients responded well to the classic treatment, not requiring a change in chemotherapy protocols, however a special attention must be paid to the particularities involved in each presentation of the same tumor in different patients.
Keywords: canine; cytology; metastasis; neoplasm; TVT